1983
DOI: 10.3758/bf03202453
|View full text |Cite
|
Sign up to set email alerts
|

Phonemic-analysis training helps children benefit from spelling-sound rules

Abstract: It has been frequently suggested that the ability to analyze spoken words into phonemes facilitates children's learning of spelling-sound rules. This research attempts to demonstrate that link by showing that phonemic-analysis training helps children take advantage of spellingsound rules in learning to read. In two experiments, preschool and kindergarten prereaders participated in an analysis condition and a control condition on each of 4 test days. In the analysis condition, children learned to segment (and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
8

Year Published

1985
1985
2009
2009

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(65 citation statements)
references
References 19 publications
3
54
0
8
Order By: Relevance
“…Outros estudos com estudantes em fase de aquisição da escrita e /ou no início da escolarização foram realizados no exterior (Goswami & Bryant, 1997;Juel, Griffith & Gough, 1986;Stanovich, Cunningham & Cramer, 1984;Treiman & Baron, 1983;Yopp, 1988, por exemplo) acerca das habilidades cognitivas como consciência fonológica, consciência sintática, memória, sequenciamento dentre outras, que podem ser preditivas do desempenho em escrita. No Brasil cabe destacar as investigações de Cardoso-Martins (1995), Maluf e Barrera (1997) (2006) acerca do desenvolvimento da habilidade em consciên-cia fonológica e o efeito sobre aquisição de leitura e escrita, dentre outros foram realizados.…”
Section: Pesquisas Sobre Escritaunclassified
“…Outros estudos com estudantes em fase de aquisição da escrita e /ou no início da escolarização foram realizados no exterior (Goswami & Bryant, 1997;Juel, Griffith & Gough, 1986;Stanovich, Cunningham & Cramer, 1984;Treiman & Baron, 1983;Yopp, 1988, por exemplo) acerca das habilidades cognitivas como consciência fonológica, consciência sintática, memória, sequenciamento dentre outras, que podem ser preditivas do desempenho em escrita. No Brasil cabe destacar as investigações de Cardoso-Martins (1995), Maluf e Barrera (1997) (2006) acerca do desenvolvimento da habilidade em consciên-cia fonológica e o efeito sobre aquisição de leitura e escrita, dentre outros foram realizados.…”
Section: Pesquisas Sobre Escritaunclassified
“…Several studies have revealed clear and specific improvements in reading ability following training in phonemic segmentation. For example, Treiman and Baron (1983) trained prereaders in segmentation skills and found that the children later showed success in reading words based on the symbolsound correspondences used in the training procedure. Hence, accumulating evidence has demonstrated that early phonemic segmentation ability may be a prerequisite for, or at least facilitate, success in early reading.…”
Section: Phonological Segmentationmentioning
confidence: 99%
“…When it is skillfully implemented, systematic code instruction is most effective for beginning and for problem readers (e.g., see Adams and Bruck 1993;Chall 1989;Liberman and Liberman 1990;and Mather 1992 for thoughtful, comprehensive reviews of the evidence). Effective instruction for beginning and for problem readers teaches them to be aware of speech sounds (phonemes) and how they are represented in the writing system (i.e., spelling-sound rules, syllable patterns) and of the meaningful units (morphemes) and their spelling patterns (Felton 1993;Juel 1988;Tunmer and Hoover 1993;Treiman and Baron 1983;Vellutino 1991b;Williams 1987). In fact, the research community is now focused on establishing a scientific base for refinements of code-emphasis intervention, including the most desirable unit of instruction (Adams 1990;Ehri and Robbins 1992;Gaskins et al 1988;Goswami and Bryant 1990;Treiman 1992), the degree to which instruction should be systematic rather than incidental (Tunmer and Hoover 1993), and the timing and emphasis of such instruction in the curriculum (Calfee 1991).…”
Section: The Nature Of Reading and Spelling Disabilitymentioning
confidence: 99%